Therapeutic Efficiency of Nasal Mucosa-Derived Ectodermal Mesenchymal Stem Cells in Rats with Acute Hepatic Failure - Wen Xiang; Xinhe Wang; Xinghui Yu; Yan Xie; Li Zhang; Naiyan Lu; Wentao Jiang (Hindawi Limited, 2023)
Background. Liver transplantation is limited by the insufficiency of liver organ donors when treating end-stage liver disease or acute liver failure (ALF). Ectodermal mesenchymal stem cells (EMSCs) derived from nasal mucosa have emerged as an alternative cell-based therapy. However, the role of EMSCs in acute liver failure remains unclear. Methods. EMSCs were obtained from the nasal mucosa tissue of rats. First, EMSCs were seeded on the gelatin-chitosan scaffolds, and the biocompatibility was evaluated. Next, the protective effects of EMSCs were investigated in carbon tetrachloride- (CCl4-) induced ALF rats. Finally, we applied an indirect coculture system to analyze the paracrine effects of EMSCs on damaged hepatocytes. A three-step nontransgenic technique was performed to transform EMSCs into hepatocyte-like cells (HLCs) in vitro. Results. EMSCs exhibited a similar phenotype to other mesenchymal stem cells along with self-renewal and multilineage differentiation capabilities. EMSC-seeded gelatin-chitosan scaffolds can increase survival rates and ameliorate liver function and pathology of ALF rat models. Moreover, transplanted EMSCs can secrete paracrine factors to promote hepatocyte regeneration, targeted migration, and transdifferentiate into HLCs in response to the liver's microenvironment, which will then repair or replace the damaged hepatocytes. Similar to mature hepatocytes, HLCs generated from EMSCs possess functions of expressing specific hepatic markers, storing glycogen, and producing urea. Conclusions. These results confirmed the feasibility of EMSCs in acute hepatic failure treatment. To our knowledge, this is the first time that EMSCs are used in the therapy of liver diseases. EMSCs are expected to be a novel and promising cell source in liver tissue engineering.